Anatomy and microsurgical relevance of the outer arachnoid envelope around the olfactory bulb based on endoscopic cadaveric observations - Kurucz, Peter; Ganslandt, Oliver; Buchfelder, Michael; Adib, Sasan Darius; Barany, Laszlo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background: Surgical approaches to the anterior cranial fossa have great risk of damaging the olfactory tract and bulb. The goal of this study was to describe the outer arachnoid envelope around the olfactory bulb which plays significant role in the approach-related injury of the nerve. Material and Methods: A total of 20 fresh human cadaveric heads were examined as a following: 5 cadaveric heads were used to describe a gross overview of the topographic anatomy of the outer arachnoid cover of the olfactory bulb. In 15 cadaveric heads endoscopic surgical approaches were performed to examine the in situ undisrupted anatomy of the outer arachnoid around the olfactory bulb. Four cadaveric heads were used for lateral subfrontal approach, 5 heads for medial subfrontal, 3 heads for median subfrontal approach and 3 heads for anterior interhemispheric approach. Results: The outer arachnoid membrane of the frontal lobe attaches the olfactory bulb strongly to the above lying olfactory sulcus. Only the most rostral portion of the olfactory bulb became slightly detached from the frontal lobe. The outer arachnoid forms a decent protrusion around the tip of the olfactory bulbs. The fila olfactoria have their own outer arachnoid cover as a continuation of the same layer of the olfactory bulb. The effect of brain retraction and manipulation forces on the olfactory bulb and the role of the here located arachnoid membranes were visually analysed and described in detail through the performed four different neurosurgical approaches. Conclusion: The results of our observations provide important anatomical details for the preservation of smelling during neurosurgical procedures.
CRIS-Team Scopus Importer:2024-12-16
Keywords: arachnoid membranes; endoscopic anatomy; microsurgical anatomy; olfactory bulb